Evaluation of the use of HbA1c in the Diagnosis of Impaired Fasting Glucose (Medico Legal Update, 2020)
Diabetes mellitus is a progressive catastrophic medical condition, associated with serious acute and chronic complications. Despite the significant improvement in the diagnostic techniques, it is estimated that up to 50% of diabetic patients are unaware of their disease, especially those with type 2 diabetes mellitus. The impaired fasting glucose, defined as fasting blood glucose 70-100 mg/dl, has been recognized as a major risk factor for the development of type 2 diabetes mellitus.Aim of the study: To investigate the use of HbA1c as an alternative to fasting blood glucose (FBG) in the diagnosis of impaired fasting glucose. Materials and methods: The study involved apparently healthy individuals, attended a private medical laboratory for routine medical checking. Two aspects were followed, dividing participants into 4 groups, group 1 with normal FBG, group 2 with FBS 100-125 mg/dl, group 3 with HbA1c < 5.7%, and group 4 with HbA1c of 5.7%-6.4 %. Group 1 and 2 were investigated for FBS, while group 3 and 4 were investigated for HbA1c.Results: A total number of 312 subjects were included in the current study, with a variable number of individuals in each group. The results of HbA1c were statistically compared with the results of FBG. The sensitivity of HbA1c in the diagnosis of impaired fasting glucose was 80%, and the specificity was 66.4% only while the positive and negative predictive values were 81.4% and 64.6% respectively.Conclusion: HbA1c should be used with caution in the diagnosis of impaired fasting glucose.